2012
DOI: 10.1097/scs.0b013e31824e2c08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Septoplasty on Mean Platelet Volume Levels in Patients With Marked Nasal Septal Deviation

Abstract: Nasal septal deviation (NSD) is a very common cause of recurrent and chronic nasal obstruction. Chronic nasal obstruction leads to increased upper respiratory tract resistance, and also upper respiratory tract resistance leads to chronic hypoxia and hypercarbic because of alveolar hypoventilation. Chronic hypoxia and hypercarbia show tendency for hypercoagulopathy.Mean platelet volume (MPV), the most commonly used measure of platelet size, is a potential marker of platelet reactivity. Large platelets that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 15 publications
1
38
1
3
Order By: Relevance
“…[7,9] It has been reported in recent studies that MPV increases in obstructive septal deviation and nasal polyps in severe adult OSAS. [6,11,12] The ratio of MPV to platelet count (MPV/PC) is a current reliable marker just like MPV. Higher MPV/PC ratio is associated with myocardial infarction, anemia, deep vein thrombosis, infective endocarditis and hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…[7,9] It has been reported in recent studies that MPV increases in obstructive septal deviation and nasal polyps in severe adult OSAS. [6,11,12] The ratio of MPV to platelet count (MPV/PC) is a current reliable marker just like MPV. Higher MPV/PC ratio is associated with myocardial infarction, anemia, deep vein thrombosis, infective endocarditis and hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…MPV level is showed to be higher in patients with pulmonary hypertension [21]. MPV shows platelet activity and large platelets are more active and have more prothrombotic potential [9].…”
Section: Discussionmentioning
confidence: 99%
“…Varol et al [24] revealed that six months of CPAP therapy caused significant reductions in median MPV values in adult patients with severe OSA. Sagit et al [9] found that septoplasty has a curative effect for hypercoagulopathy with reducing MPV values. Kucur et al [25] found that MPV values were found to be higher in children with AH than controls and there was a significant reduction in MPV levels after adenoidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, increasing MPV levels have been associated with the prognosis of some diseases including such as hypertension, unstable angina pectoralis, neurological diseases, autoimmune diseases and obstructive sleep apnea. [8][9][10][11][12][13][14][15] MPV may be used as a marker that indicates chronic intermittent hypoxia. In the study of Somuk et al 16 reported that MPV parameter was found high in the children with chronic effusion otitis media.…”
Section: Introductionmentioning
confidence: 99%